Who moved my eggs? An experimental test of the egg arrangement hypothesis for the rejection of brood parasitic eggs - Hanley, Daniel; Samaš, Peter; Hauber, Mark E; Grim, Tomáš (Animal cognition, 2015)
Avian brood parasitism is an exceptional reproductive strategy whereby parasites reduce their own costs associated with parental care and impose them on the host parents. Consequently, host species have evolved multiple defensive mechanisms to combat parasitism. The vast majority of research attention to date has examined host defenses to recognize and reject parasitic eggs. The recently proposed "egg arrangement hypothesis" suggests that hosts may not focus solely on individual eggs' features, but instead the overall arrangement of the clutch may also provide a cue that parasitism has occurred. Correlative data revealed that host females maintaining a consistent egg arrangement across the incubation period were more likely to reject foreign egg models than females that did not keep a consistent egg arrangement. Here, we provide the first experimental test of this hypothesis in the European blackbird (Turdus merula). We experimentally parasitized nests such that the egg arrangement was either disrupted or not disrupted. We found no evidence that altered egg arrangement was used as a cue for egg rejection by host females. Therefore, we suggest that females that keep consistent egg arrangement are more likely to eject foreign eggs for other correlated reasons. Thus, egg arrangement does not serve as an independent cue to trigger egg rejection responses to parasitism in this host species.
Keywords: ovum; zpěvní ptáci; Female; Host-Parasite Interactions; Animals; Songbirds; ženské pohlaví; Nesting Behavior; interakce hostitele a parazita; Ovum; zvířata; hnízdění